Implementation of Think Pair Share during Limited Face-to-Face Learning to Improve Students’ activeness, Concept Understanding, and Learning Outcome - Siti Nur Jamilatul Hasanah; Vinka Daniyah Salsabila; Imam Rofiki (Abjadia, 2022)
Activeness and concept understanding during limited face-to-face learning needs to be studied. This study is reviewed from the activeness, concept understanding, and student learning outcome through the Think Pair Share learning model with several actions. Classroom action research with a qualitative approach was carried out on a public junior high school at Pasuruan, Indonesia with 16 grade 8 students as research subject. The instruments of this research were test, observation sheet, and documentation. Data analysis was carried out by describing the activeness, concept understanding, and student learning outcome. The results show that there was a significant increase in the activeness and concept understanding so that student learning outcome also increase by using Think Pair Share during limited face-to-face learning.